Evaluating the Effectiveness of the Supportive Parenting App on Parental Outcomes: Randomized Controlled Trial - Shefaly Shorey; Evelyn Law; Jancy Mathews; Siew Hoon Lim; Luming Shi; Jing Shi Chua; Ruochen Du; Yiong Huak Chan; Thiam Chye Tan; Cornelia Chee; Yap Seng Chong (JMIR Publications, 2023)
BackgroundAdjusting to new or additional parenting responsibilities increases stress and affects parental well-being. Existing research has highlighted both parents' desire to receive more support. It has also been found that receiving sufficient social support enhances parenting outcomes. With the increasing popularity of mobile health apps, a Supportive Parenting App (SPA) intervention was developed to fulfill the support needs of parents during the perinatal period. ObjectiveThis study aimed to examine the effectiveness of the SPA on parental outcomes during the perinatal period. MethodsA 2-group pretest and repeated posttest randomized controlled trial was conducted wherein 200 couples (N=400 mothers and fathers) were recruited from 2 public health care institutions in Singapore. Parents were randomly assigned to intervention (100/200, 50%) or control (100/200, 50%) groups. The SPA intervention consisted of a mobile app-based psychoeducation and peer support program to support parents from pregnancy to 6 months post partum. The outcome measures included postnatal depression, anxiety, parental bonding, parental self-efficacy, perceived social support, and parenting satisfaction. Data were collected at baseline (at >24 weeks of gestation-age of viability in Singapore) and at the first, second, fourth, sixth, ninth, and 12th month post partum. Linear mixed models were used to compare parental outcomes between the groups, and a linear mixed model for repeated measures was used to examine within-group changes. ResultsParents in the intervention group mostly showed better outcomes compared with those in the control group. Parents in the intervention group had higher perceived social support than those in the control group at the first (effect size=1.59, 95% CI 0.38-2.80; Cohen standardized effect size=1.31; P=.01), second (effect size=1.98, 95% CI 1.09-2.88; Cohen standardized effect size=2.21; P=.003), and fourth (effect size=2.57, 95% CI 1.62-3.51; Cohen standardized effect size=2.72; P=.048) months post partum. However, parents in the intervention group showed significantly poorer parental bonding (effect size=1.67, 95% CI 0.24-3.11; Cohen standardized effect size=1.16; P=.02). The other parental outcomes did not differ significantly between groups. The scores of mothers and fathers also differed significantly for all outcomes except parental self-efficacy. ConclusionsParents in the intervention group generally fared better, especially regarding perceived social support. However, the lack of statistical significance in most outcomes showed the limited effectiveness of the SPA intervention, which may be because of the COVID-19 pandemic. Parental differences in outcome scores suggest that mothers and fathers have different support needs; therefore, interventions should be tailored accordingly. Further improvements and evaluations are needed to examine the effectiveness of the SPA intervention in enhancing parental outcomes. Despite statistically insignificant results, limitations should be considered to further improve mobile health app-based interventions such as SPA, as they could serve as reliable and convenient sources of support for parents. Trial RegistrationClinicaltrails.gov NCT4706442; https://clinicaltrials.gov/ct2/show/NCT04706442